Analisa Pemberian Berbagai Jenis Pupuk Organik Padat Terhadap Pertumbuhan dan Produksi Tanaman Sawi Pakcoy (Brassica rapa L.) Organik - Septi Anggraeni; Mariyatul Qibtiyah; Dian Eka Kusumawati; Emmy Hamidah (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Pakcoy mustard plant is a plant that is easily cultivated by farmers in Indonesia. Pakcoy mustard plants are very valuable economically because people want them. In addition to having many health benefits, pakcoy mustard plants also have a short cultivation frequency, to increase good production yields, you must pay attention to cultivation methods starting from the land processing process to harvest. Thus, the aim of this research was to examine the impact of different solid organic feltilizers ob the development and yield of organic pakcoy mustard plants. This research was designed with a regular randomized group design (RAK) consisting of seven treatments, including: No treatment, organic fertilizer application of burnt husk, fertilizer application of vermicompost, fertilizer application of chicken manure, fertilizer application of cow dung, fertilizer application of goat dung and fertilizer application of bat dung. The results of the research on this study are that it can increase the productivity of pakcoy mustard plants and the best results are found in the provision of solid organic fertilizer treatment of burnt husks.